The rocky road trip of Lydia Goldblatt & Julie Graham-Chang - Ignatow, Amy (Amulet Books, 2012)
It's summertime, and Julie and Lydia are going on a road trip! After all the ups and downs of their first year in junior high, they're looking forward to seeing the sights and getting some new perspective on their quest for popularity. Full color.